1992
DOI: 10.1002/tea.3660290604
|View full text |Cite
|
Sign up to set email alerts
|

A curriculum strategy that expands time for in‐depth elementary science instruction by using science‐based reading strategies: Effects of a year‐long study in grade four

Abstract: An integrative curriculum strategy emphasizing science process skills and hands‐on activities expanded the time allocated for in‐depth science instruction by replacing a district‐adopted basal reading program with science‐content reading designed to facilitate applied comprehension skills. This study investigated the combined effect of these curricular components (i.e., in‐depth science, science‐content‐based reading) upon student achievement, attitudes, and self‐confidence in both science and reading over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 4 publications
5
46
0
2
Order By: Relevance
“…In a systematic review on quasi-experimental studies of integrated scienceliteracy instruction, Bradbury (2014, p. 483) noted that the reviewed studies "indicated positive outcomes for student achievement in both science and reading, as well as for affective factors". For example, in Romance and Vitale's (Romance & Vitale, 1992;Vitale & Romance, 2012) In-Depth Expanded Applications of Science (IDEAS) model of integration, traditional language arts instruction was replaced with joint science-reading instruction in grades 1 to 5. Central to the IDEAS model was a focus on core science concept instruction that involved firsthand experiences, reading comprehension, use of science process skills, and journal writing.…”
Section: Integrated Science-literacy Instructionmentioning
confidence: 99%
“…In a systematic review on quasi-experimental studies of integrated scienceliteracy instruction, Bradbury (2014, p. 483) noted that the reviewed studies "indicated positive outcomes for student achievement in both science and reading, as well as for affective factors". For example, in Romance and Vitale's (Romance & Vitale, 1992;Vitale & Romance, 2012) In-Depth Expanded Applications of Science (IDEAS) model of integration, traditional language arts instruction was replaced with joint science-reading instruction in grades 1 to 5. Central to the IDEAS model was a focus on core science concept instruction that involved firsthand experiences, reading comprehension, use of science process skills, and journal writing.…”
Section: Integrated Science-literacy Instructionmentioning
confidence: 99%
“…In adapting a cognitive-science-based, instructional model (Science IDEAS) that has been shown effective (Romance & Vitale, 1992, 2006 in accelerating science understanding and reading comprehension proficiency of older children in grades 3-5, this study addressed a recognized need to develop student science understanding and comprehension proficiency at the primary levels (French, 2004;Gelman & Brenneman, 2004) in a fashion that would raise school achievement expectations for both at-risk and non at-risk students.…”
mentioning
confidence: 99%
“…The National Reading Panel (2000, p. 464) recognized the original grade 3-5 Science IDEAS study (Romance & Vitale, 1992) as one of the few scientifically-based research studies demonstrating combined student achievement in science and reading comprehension. Romance and Vitale (2001) replicated and extended their initial study over an additional two-year period and obtained the same achievement outcomes in science and reading.…”
mentioning
confidence: 99%
“…Nastava prirodnih nauka ima specifičnu ulogu da doprinese funkcionalnoj pismenost čitanjem tekstova iz nauke, koji imaju svoje žanrovske specifične karakteristike. Istraživanja i interventni programi za podršku razvoja veštine čitanja s razumevanjem koncipirani na aktivnostima u nastavi prirodnih nauka pokazuju da je to moguće (Romance & Vitale, 1992;Vitale & Romance, 2007). U jednom od programa učenici su praktikovali brojne aktivnosti rada na tekstu (čitanje i pisanje) u kontekstu smislenog učenja prirodnih nauka.…”
Section: Podrška Razvoju Bazične Funkcionalne Pismenostiunclassified